2019
DOI: 10.3390/md17120703
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Optimization of Fermentation Conditions, and Characterization of an Exopolysaccharide from Pseudoalteromonas agarivorans Hao 2018

Abstract: In recent years, the wide application of exopolysaccharides (EPSs) in food, cosmetics, medicine, and other fields has drawn tremendous attention. In this study, an EPS produced by Pseudoalteromonas agarivorans Hao 2018 was isolated and purified, and its fermentation conditions were optimized. Its structure and biological functions were also studied. The purity and molecular weight of EPS were determined by high performance liquid chromatography (HPLC), and the EPS exhibited a number average of 2.26 × 10 5 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 40 publications
(38 reference statements)
1
16
0
Order By: Relevance
“…This increase in PMM expression is accompanied by a decrease in PGM expression levels, thereby increasing the conversion of glucose-6-P to mannose-1-P, ultimately leading to increased GDP-l-fucose production in the strain (Ju et al, 2022). EPS from P. agarivorans have previously been reported to exhibit good antioxidant activity (Hao et al, 2018). PGM has recently been shown to play a major role in xyloglucan catabolism in the anaerobic Gram-positive bacterium Ruminiclostridium cellulolyticum, where it converts…”
Section: Discussionmentioning
confidence: 99%
“…This increase in PMM expression is accompanied by a decrease in PGM expression levels, thereby increasing the conversion of glucose-6-P to mannose-1-P, ultimately leading to increased GDP-l-fucose production in the strain (Ju et al, 2022). EPS from P. agarivorans have previously been reported to exhibit good antioxidant activity (Hao et al, 2018). PGM has recently been shown to play a major role in xyloglucan catabolism in the anaerobic Gram-positive bacterium Ruminiclostridium cellulolyticum, where it converts…”
Section: Discussionmentioning
confidence: 99%
“…The EPS in deionized water was further purified by using DEAE-52 anion-exchange chromatography and gel filtration chromatography [50]. Then, the purified EPS was dialyzed with deionized water and selective semipermeable membranes (8000~14,400 da) [17]. The polysaccharides were freeze-dried and stored at 4 • C, and labeled as P7, P8, and P9, respectively.…”
Section: Extraction and Purification Of Epss Under Different Fermentation Conditionsmentioning
confidence: 99%
“…In addition, EPSs from marine bacteria have marked anti-tumor, antiviral, and immunomodulatory functions [15]. Previous studies have shown that the exopolysaccharide produced by P. agarivorans Hao 2018 has good antioxidant activity, hygroscopicity, and moisture retention, and also has good absorption of Cu 2+ and Pb 2+ [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The carbohydrate content of EPS from P. agarivorans stain Hao 2018 (yield 4.5 g/L) isolated from Yellow Sea of China contained 90% glucose and 6% mannose. The main biological activity of this strain was moisture retention and absorption of free radicals (i.e., antioxidant) with potential applications in food and cosmetics industries (Hao et al, 2019 ). Pseudoalteromonas sp.…”
Section: Marine Biosurfactant-producing Bacteriamentioning
confidence: 99%